The perception of fungi among Karajá indigenous children and adolescents from Brazil - Mazulkieliche Jeronimo dos Reis; Lucas Leonardo-Silva; Solange Xavier-Santos (BMC, 2024)
Abstract Background Environmental perception involves the interpretation and interaction of individuals with their surroundings, influenced by cultural, social, and individual factors. Analyzing the environmental perception of children and adolescents contributes to fostering awareness and ethical behavior toward the environment. Indigenous communities, such as the Karajá from Brazil, possess significant environmental knowledge due to their connection with nature, providing distinctive insights into biodiversity and natural interconnections. In this study, the perception of fungi among Karajá indigenous children and adolescents was investigated. Methods The study involved 229 elementary school students from the Macaúba, Fontoura and Santa Isabel do Morro communities, located on Bananal Island, Brazil. Students were encouraged to draw what they knew about fungi and answer where they learned about fungi and what name they give to these organisms. The drawings were analyzed considering seven categories. Results The term most used to refer to fungi was hedoro(u) (56%), followed by fungus (21%) and mushroom (11%). Most students said they had learned about fungi in nature (38%) and at school (36%). The most represented organisms were in fact fungi (93%), mainly being portrayed in nature (94%). Most participants did not attribute any ecological function to fungi (83%), although 16% of them recognized fungi as decomposers and 1% as phytopathogenic agents. Negative aspects, particularly food contamination, were more frequently represented (13%) than positive aspects (4%). The drawings identified two morphological types: mushrooms (87%) and mold (13%). Among these mushrooms, 68% possibly represent the Amanita muscaria species. Conclusions Although the children and adolescents showed that they noticed the fungi around them, the group's concept and understanding were limited to the figure of the mushroom and the negative aspects related to food contamination. Strong association of the fungi with the A. muscaria is noteworthy, since it does not occur in the environment in which the participants live, suggesting that external stimuli, such as TV or the internet, can influence their perception more than the nature they are exposed to.